Equality of Strategy and Resources in Plastic Packaging Industry Companies Case Study : PT. Sinergi Inti Plastindo Tbk - Khoirun Nisa Bahri (CV. AFDIFAL MAJU BERKAH, 2022)
This study aims to identify a strategic group model in the plastic packaging industry in Indonesia. The plastic packaging industry plays an important role in the manufacturing industry. With the increasing demand for a manufactured product, the plastic packaging industry is still very tempting for business people. Strategic Group is a number of business units or a number of companies that use the same strategy with the same resources. This research focuses on PT. Sinergi Inti Plastindo, Tbk a plastic packaging company in Indonesia. The company produces various types of plastic packaging for food products. This case study research method is also used to describe a strategy used by companies as a strategy to deal with competition in industrial groups. The results of the research show that the market leader holds the highest sales in 2019 using the same strategy as its competitors. The results also show that companies operating in the same industry need to develop their product types. Don't just focus on one type of product. The number of types of products produced will increase the sales of the company. In addition, the market share obtained by the company will be higher.